Multifunctional Dendrimer Formation Using Thiolactone Chemistry. Issue 18 (21st February 2017) - Kaya, N. Uğur; Du Prez, Filip E.; Badi, Nezha
Abstract : A thiolactone‐based strategy is conducted to prepare multifunctional dendrimers. In this context, a thiolactone bearing an isocyanate function is reacted with a hydroxyl terminal groups of a 4‐arm poly(ethylene glycol) (step 1). Aminolysis of the thiolactone ring and subsequent thiol‐acrylate reaction leads to a double functionalization (step 2). Repetition of steps 1 and 2 leads to the formation of multifunctional dendrimers. Abstract : Thiolactone chemistry is a powerful tool for the design of complex multifunctional architectures. In this study, this versatile click‐inspired synthetic strategy is conducted to prepare multifunctional dendrimer‐like structures. For this purpose, a thiolactone bearing an isocyanate function, prepared in multigram scale, is utilized for multiple step functionalization starting from a 4‐arm star‐shaped poly(ethylene glycol). Amine‐thiol‐acrylate conjugation is carried out in order to form the aforementioned structures. The efficient aminolysis of the thiolactone ring and the reaction of the generated thiol with the double bond of an acrylate derivative are completed in a one‐pot procedure. The choice of the amine and/or acrylate derivatives can allow the introduction of different functional groups for each new generation, potentially leading to multivalent dendrimer‐like structures.